Present but not detected: new records increase the jaguar's area of occupancy in the coastal Atlantic Forest. Issue 1 (4th August 2022) - Fusco-Costa, Roberto; Ingberman, Bianca; Shimokawa Magezi, Gabriel; Leite de Araujo Monteiro-Filho, Emygdio
Abstract: The jaguar Panthera onca has lost 85% of its habitat in the Atlantic Forest, where it persists in small and isolated populations in the largest fragments. In the absence of recent records, the jaguar had previously been presumed extinct in the large Atlantic Forest fragments of the Serra do Mar in southern Brazil. However, as this region is mountainous, densely forested and difficult to access, the jaguar could still be present, but undetected. We carried out an intensive survey using camera traps and interviews with local people in a large (c. 6, 500 km 2 ) forest block. During 2011–2019, 98 camera-trap stations were established (14, 239 trap-days), and 249 interviews were conducted in 102 grid cells of 5 × 5 km. We obtained the first images of the jaguar in the region, from which five individuals were identified, and interviewees provided records of the jaguar in 24 grid cells. Our findings increase the range of this species in the Atlantic Forest by 9%, and we recommend that the area should be classified as a jaguar conservation unit. As the area we surveyed is adjacent to the Serra do Mar jaguar conservation unit, the combined area of 19, 262 km 2 is the largest priority area for jaguar conservation in the Atlantic Forest. This proposed jaguar conservation unit could serve as a vital source of jaguar individuals for the coastal forests further south. We recommend that surveys are extended southwards to Santa Catarina state to determine whether the presumed extinction of jaguars in this state is another case of a false absence.